Development and Operationalization of a Model of Innovation Management System as Part of an Integrated Quality-Environment-Safety System - Dorin Maier; Irmer Sven-Joachim; Astrid Fortmüller; Andreea Maier (Amfiteatru Economic Journal, 2017)
The results of the research, presented in this article, have the purpose to contribute in the area of innovation management and its relation to other management systems. The research objective is to give to organizations a model of innovation management system as part of an integrated management system. Defining the model of innovation management system is based on the four perspectives of the balanced scorecard tool, namely: financial perspective, learning and development, internal processes and customers. In the process of defining the model several steps were taken, such as: literature review, data collection from the enterprise level through a questionnaire, analysis and correlation of data and finally the proposed model has been operationalized. In order to have a working model that can be easily adopted by any interested company, the research was deepen to the organizational processes, identifying nine processes specific for innovation that exist in an organization. Each of the nine processes have been operationalized using a SIPOC model (Suppliers - Inputs - Process - Outputs - Customers). The system for managing innovation may therefore have a positive influence on the ability and awareness of enterprises in innovation actions, and by defining this model the research conducted in this article helps to improve the efficiency of innovation, with direct implications in business performance.
Keywords: O32; M21; 330; integrated management systems; innovation management system; quality management system; the performance of organizations